Spacing Education Networks in Modern Russia - Irina Abankina (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The article considers the spacing of education networks under the conditions of demographic shrinking and negative tendencies in populationdistribution. A successful restructuring of education institutions necessitates the creation of integrated education structures that should also include other social, cultural, and sport organizations.The article argues that in order to increase the accessibility of quality state and municipal social-cultural services it is necessary to take the following steps:To introduce the node-based model of a network, instead of the extant hierarchical one;To organize student transportation to education institutions;To introduce local network management instead of centralized management;To introduce integrated institutions.To provide an optimal legal basis for the integration of educational and social-cultural resources, a Federal Law On the Integrated State or Municipal Social Institution should be adopted in order to introduce the necessary regulations.